2004
DOI: 10.1093/alcalc/agh058
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End-Products in Patients With Chronic Alcohol Misuse

Abstract: Our findings suggest a more complex relationship among advanced glycation, oxidative stress and metabolism of ethanol and their link to nutrition and nutrition-associated parameters. AGE as a result of oxidative stress might be similarly linked to increased cardiovascular risk of heavy alcohol drinkers, as are malnutrition and inflammation; however, further studies are needed to confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…However, while leptin is sensitive to several physiological stimuli including feeding status (fasted vs. fed) and body weight, nutrient status was infrequently reported or controlled for and correlations between body weight and leptin were not always performed. Similar to the inconclusive results reported for circulating leptin in animal models, the serum leptin concentration from humans appears to be unrelated to alcohol intake [80,87,95,96,97,98,99], although exceptions do exist [27,100,101,102]. In alcoholic patients, leptin has been reported to be increased, decreased or unchanged, and serum leptin was also not altered by either alcohol withdrawal for 15 days [27] or the severity of liver disease [87,95,96].…”
Section: Adipokinessupporting
confidence: 65%
“…However, while leptin is sensitive to several physiological stimuli including feeding status (fasted vs. fed) and body weight, nutrient status was infrequently reported or controlled for and correlations between body weight and leptin were not always performed. Similar to the inconclusive results reported for circulating leptin in animal models, the serum leptin concentration from humans appears to be unrelated to alcohol intake [80,87,95,96,97,98,99], although exceptions do exist [27,100,101,102]. In alcoholic patients, leptin has been reported to be increased, decreased or unchanged, and serum leptin was also not altered by either alcohol withdrawal for 15 days [27] or the severity of liver disease [87,95,96].…”
Section: Adipokinessupporting
confidence: 65%
“…Kalousová et al (2004) reported markedly increased AGE in chronic alcoholics compared to healthy controls [304]. Moreover, their results also supported the notion that AGE production may be prevented or even diminished by antioxidant supplementation with vitamin B derivatives [305,306], and/or vitamins A, C, and E [307].…”
Section: Lifestyle Factorsmentioning
confidence: 81%
“…Advanced glycation end products (AGEs), a heterogeneous group of irreversible reactive derivatives formed by non-enzymatic glycation and oxidation of proteins and lipids, elicit oxidative stress generation, subsequently evoke inflammation [2], and have been implicated in pulmonary [3] and renal fibrosis [4]. AGE levels are elevated in nonalcoholic steatohepatitis patients (NASH) [5] and chronic alcohol misuse patients [6,7]. There are no data on AGE levels in hepatitis C patients; however, AGE levels independently correlate with IR [8].…”
Section: Introductionmentioning
confidence: 99%